Acoustic Properties of Waste Particle Mixed Polyurethane Composites - KÜÇÜK, HALUK (SAGE PUBLICATIONS LTD, 2014)
A variety of particles were mixed with polyurethane-based matrix to develop functional composites. Adding marble, steel, prina (olive oil extraction) and sand particles into PU foam increases sound absorption characteristics of the material. Best results were obtained with marble and steel particles. Marble particles improved high frequency characteristics better than steel particles. Increasing the amount of prina particles enhanced mid-to-high frequency sound absorption properties. Acoustic properties of sand mixed composites were increased to its optimal rates by adding 25% particles into the polyurethane matrix.
Keywords: Polyurethane; Foam; Marble; Steel; Prina; Sand; Sound absorption; SOUND-ABSORPTION; MECHANICAL-PROPERTIES; FIBER; FOAM; POLYOL